Examination of International Fisheries’ Agreements with Game Theoretic Approaches - Szendrey, Orsolya; Karcagi-Kováts, Andrea (International Journal of Engineering and Management Sciences, 2020)
Nowadays, the application of game theoretic approaches is becoming more and more popular in different types of resource management problems. Overfishing is a growing problem worldwide and well known from literature. Unfortunately the tragedy of commons could be observed in several empirical studies in the case of international fisheries. In our paper, we focus on the examination of international agreements related the fisheries’ management (with special focus on the issues of overfishing) using game theoretic approaches. We review the history of fisheries’ agreements and the main game theoretic results, well known from literature. We highlight the main types of games applied in the previous research studies and summarize the main results related to the outcome and the stability of the game. To this topic better understood, certain empirical examples are introduced as well.